Modeling temperature profile in mass concrete at early ages of cement hydration - Donald Chidiebere, Ugwuanyi; Fidelis Onyebuchi, Okafor (International Journal of Engineering and Technology, 2021)
Thermally induced cracks due to temperature gradient in mass concrete have adverse effects on its durability and service life. Heat released during the hydration of Portland cement in early age mass concrete can be quite excessive depending on the ambient temperature, cement content of the concrete mix and the size. Finite difference model using Crank Nicholson implicit method was developed based on the two dimensional unsteady state heat conduction. Optimized MATLAB based software was developed for simulation and data visualization. A mass concrete block cast with standard mix ratio and water cement ratio was used to verify the efficacy of the model. Type-K thermocouple and digital thermometer were used to monitor the temperature at time intervals. The temperature profile showed a hotter core and cooler surface except for the initial placement temperature, which exhibited a uniform temperature for all thermocouple locations. Peak temperature values were recorded within the first day of concrete placement. The model successfully predicted the temperature profile of the mass concrete at early ages of cement hydration. With the knowledge of the ambient temperature and the configuration of the mass concrete, the model can reliably predict the temperature profile from which potential for thermal cracks occurrence can be determined to enable suitable proactive preventive and control measures.Â Â